Highway pavement maintenance optimisation using HDM-4: a case study of Morocco's arterial network. Issue 10 (24th August 2022) - Bannour, Abdelilah; El Omari, Mohamed; Khadir Lakhal, El; Afechkar, Mohamed; Joubert, Pierre
ABSTRACT: One of the key objectives of a pavement management system (PMS) is to find the optimal maintenance strategy, which minimises the sum of a road agency and user costs by maximising the net benefit to society. The PMS helps road agencies to better apply a selection of the right pavement treatments. The objective of the present paper is to show how the HDM-4 (Highway Development and Management 4) approach allows to develop a policy road leading to the optimal and robust selection of maintenance strategies under budgetary constraints, which minimises the sum of agency costs and road user costs in present value or maximises the net benefit to society over an analysis period. The findings could help road agencies to better apply the right pavement treatments. The present study is based on the exploitation of road network data, obtained from pavement structural condition survey and performed by the National Studies and Road Research Center. The study applies a long-term simulation (20 years) of maintenance budget needs under different budget scenarios.